COMMUNICATION STRATEGIES OF KOMISI PEMILIHAN UMUM KOTA MAKASSAR IN INCREASING PUBLIC PARTICIPATION IN THE PILKADA 2020 DURING THE COVID-19 PANDEMIC - Marwah; M. Tahir; Murni Mahmud (International Journal of Business English and Communication, 2024)
This research discusses the Communication Strategy of the Komisi Pemilihan Umum (KPU) of Makassar City in increasing public participation during the Covid-19 Pandemic. The background of the formation of this research is because the Regional Head Election (Pilkada) was held in the midst of the Covid-19 pandemic whose transmission was very fast, so the government appealed to keep a distance and do activities at home to prevent the transmission and spread of Covid-19. This is inversely proportional to the Pilkada, which is actually a people's democratic party that usually gathers a lot of masses to gain support. This research uses Qualitative methods with a case study approach by using the theory of determining communication planning strategies by Harold D. Laswell. The results of the study are (1) KPU Kota Makassar establishes a number of human resource chains (organizers) that carry out socialization to the community to disseminate information about elections, (2) KPU Kota Makassar compiles and provides electoral messages that are informative, persuasive, and educative to the public, (3) Using social media, conventional media, and associating influencers to disseminate electoral information, (4) Socialization by targeting 10 strategic bases, socialization in the Sangkarrang Islands and on Lae-lae Island, embracing communities, and socialization with all the people of Makassar City who can already cast their votes.